Development of circulating isolates of Plasmodium falciparum is accelerated in Anopheles vectors with reduced reproductive output. - Kristine Werling; Maurice A Itoe; W Robert Shaw; Raymond Dombagniro Hien; Bali Jean Bazié; Fofana Aminata; Kelsey L Adams; Bienvenu Seydou Ouattara; Mathias Sanou; Duo Peng; Roch K Dabiré; Dari F Da; et al. (Public Library of Science (PLoS), 2024)
Anopheles gambiae and its sibling species Anopheles coluzzii are the most efficient vectors of the malaria parasite Plasmodium falciparum. When females of these species feed on an infected human host, oogenesis and parasite development proceed concurrently, but interactions between these processes are not fully understood. Using multiple natural P. falciparum isolates from Burkina Faso, we show that in both vectors, impairing steroid hormone signaling to disrupt oogenesis leads to accelerated oocyst growth and in a manner that appears to depend on both parasite and mosquito genotype. Consistently, we find that egg numbers are negatively linked to oocyst size, a metric for the rate of oocyst development. Oocyst growth rates are also strongly accelerated in females that are in a pre-gravid state, i.e. that fail to develop eggs after an initial blood meal. Overall, these findings advance our understanding of mosquito-parasite interactions that influence P. falciparum development in malaria-endemic regions.